Viewing angle Effect on Gait Recognition Using Joint Kinematics - Charalambous, C.C; Bharath, A.A (6th International Conference on Imaging for Crime Prevention and Detection (ICDP-15), 2015)
Gait offers some advantages as a biometric; it can be applied at a distance, and without a subject's cooperation. There are several factors that influence the accuracy of gait recognition methods. This study investigates only the effect of relative camera-subject viewing angle. We focus on model-based approaches, particularly using joint kinematics. Our results support intuition: capturing the subject from side views provides the best accuracy, and accuracy decays in moving away from fully side-on views, both in the longitudinal and latitudinal directions. Subjects are well-separable when captured from an elevation angle of up to 65°.